Peranan Guru dalam Perspektif Pendidikan Islam - Nashihin Nashihin; Musbikhin Musbikhin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
Teachers or educators have a very strategic and core position in educational activities. They require intelligence, maturity, moral nobility, sincerity of heart and much more. The type of research used in this research is library research which consists of two types of data, namely primary and secondary. Primary data were obtained by researchers from books on Islamic Education, while secondary data were supporting data in this study, namely data from research results related to the problems the authors examined. The research results are as follows : In Islam, educators are those who are responsible for the development of students. In Islam, the most responsible person is the parent of the child. The emergence of teachers with all their roles, because of the fact that parents are no longer possible to be educators for their children. This happens along with the development of science and technology that must be mastered by each generation. In order for each generation to receive good education and teaching that can help the growth and development of children, professional teachers are needed, where professional teachers are required to have many requirements and competencies in order to carry out their duties properly. Once the role and responsibility of a teacher is so great, Islam gives a very high award for the teaching profession, which is equated with the prophets and apostles. The Islamic view of the teacher is so noble that it is promised for a teacher that he will receive prayers from the inhabitants of the sky and the inhabitants of the earth, he is prayed for for safety and happiness.